Torilis pseudonodosa Bianca (Apiaceae) – new species for the flora of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
We report the first record of Torilis pseudonodosa Bianca (Apiaceae) from Ukraine. It was found on 28th of May 2021 in the “Potiivska” section of the Black Sea Biosphere Reserve near the village of Zaliznyi Port (Southern Ukraine). Torilis pseudonodosa previously was known from various countries in the Mediterranean Basin and Western Asia, but not from Ukraine nor elsewhere in Eastern Europe. We discovered a hitherto unknown population of Torilis pseudonodosa during the 15th EDGG Field Workshop, an international expedition of the Eurasian Dry Grassland Group (EDGG) taking place in Southern Ukraine, from 23 May to 2 June 2021. We present the taxon, its morphology and general distribution, describe its first Ukrainian site ecologically and coenologically and provide photos of the site and the species. The species occurred in a saline steppe, close to the Black Sea coast. The vegetation was dominated by Agropyron pectinatum and Halimione verrucifera, with Artemisia santonica, Festuca callieri agg., Milium vernale and Vicia hirsuta as subdominants. The classification of the saline steppe of the “Potiivska” section of the Black Sea Biosphere Reserve near is problematic, because species composition represents a mixture of steppic and halophytic plants. A definitive decision would require comprehensive phytosociological analyses. Since there was no indication of anthropogenic influence at the site, we assume that Torilis pseudonodosa reached it as a result of natural migration of its propagules (e.g. with birds). Thus, the species can be considered as nonsynathropic in the flora of Ukraine.
Keywords: new find, migration, Black Sea Biosphere Reserve, Mediterranean region.